Analysis of the Effect of Service Quality on the Interest of Outpatients to Visit the Main Clinic Bali Sudirman Medical Centre Denpasar City in 2023 - Santommy, Charlie; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Clinical health services as one of the service fields that play an important role. Based on the results of interviews with 15 patients, it was shown that all patients were still dissatisfied with the services provided so that they were not interested in making a follow-up visit. The purpose of this study is to determine the influence of service quality on outpatient revisit interest. The research design used in this study is an analytical survey with a cross sectional approach. The population in this study was 252 patients and the sample taken by Purposive sampling was 155 people. The data collection methods are primary data, secondary data and tertiary data. The data analysis used is a logistic binary regression test. The results showed that the profession had a sig-p value of 0.000 < 0.05, safety sig-p 0.002 < 0.05, satisfaction sig-p 0.003 < 0.05, and sig-p facilities 0.000 < 0.05 which means that it has an influence on the interest of patient revisit. The efficiency variable has a sig-p value of 0.158 > 0.05, which means that efficiency has no effect on the patient's interest in revisiting. The conclusion in this study is that there is an influence of professionalism, safety, satisfaction and facilities on the interest of outpatient return visits, while efficiency has no effect on the interest of outpatient return visits. Suggestions for clinics are expected to be a reference to better understand the importance of service quality in accordance with the regulations of the Ministry of Health in order to improve the health services provided to patients to the maximum.